Thermochemistry of chromone- and coumarin-3-carboxylic acid - Agostinha A R Matos (2010)
The standard (pA(0)A = 0.1 MPa) molar enthalpies of formation in the condensed state of chromone-3-carboxylic acid and coumarin-3-carboxylic acid were derived from the standard molar energies of combustion in oxygen at T = 298.15 K, measured by combustion calorimetry. The standard molar enthalpies of sublimation were obtained by Calvet microcalorimetry. From these values the standard molar enthalpies in the gaseous phase, at T = 298.15 K, were derived. Additionally estimates of the enthalpies of formation, of all the studied compounds in gas-phase, were performed using DFT and other more accurate correlated calculations (MCCM and G3MP2), together with appropriate isodesmic, homodesmic or atomization reactions. There is a reasonable agreement between computational and experimental results.